ANALISIS KUALITAS AIR UNTUK MENDUKUNG PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) PADA TAMBAK BUDIDAYA - Andriani, Riska; Mawardi, Isaiah Imam (Prodi Biologi Universitas PGRI Ronggolawe, 2025)
Vannamei shrimp (Litopenaeus vannamei) is one of the leading aquaculture commodities in Indonesia due to its high adaptability to environmental fluctuations and rapid growth rate. However, the success of vannamei shrimp farming largely depends on water quality. This study aimed to analyze water quality parameters, including temperature, pH, salinity, and dissolved oxygen (DO), to support optimal growth of vannamei shrimp in aquaculture ponds. Water quality parameters were measured twice daily at 12:00 PM and 8:00 PM. The results showed that water temperature ranged between 27°C–32°C, pH between 7.8–8.0, salinity between 15–20 ppt, and DO between 4–5 mg/L. All parameters were within the ideal range for vannamei shrimp growth. However, a decline in water quality during the dry season affected shrimp harvests, with a production decrease to 2.33 tons compared to 2.48 tons during the rainy season. This indicates that water quality, particularly salinity, can influence shrimp productivity. The implementation of water quality management strategies, such as routine parameter monitoring, the use of aerators, and water volume regulation, proved effective in maintaining optimal conditions for vannamei shrimp cultivation in ponds.